Study of an extended family with CTLA-4 deficiency suggests a CD28/CTLA-4 independent mechanism responsible for differences in disease manifestations and severity - Hou, Tie Zheng (Clinical immunology (Orlando, Fla.), 2018)
Copyright © 2018 Elsevier Inc. All rights reserved.